PSIII-31 Standardized ileal digestible lysine requirement of Ross 308 broilers at the age of 10 to 21 days. (7th December 2018) - An, S; Kong, C
Abstract: A total of 720 10-day-old Ross 308 broilers (297.4g ± 22.34) were used for an 11-day growth trial. The birds were allocated to 6 diets and 8 blocks with a randomized complete block design to estimate the standardized ileal digestible (SID) lysine requirement. The 6 experimental diets were based on corn-soybean meal, and the concentrations of SID lysine in the diets increased equally from 0.83% to 1.39% with a consistent concentration of all amino acids except for lysine. As the SID lysine increased, both body weight gain (BWG) and gain:feed increased linearly and quadratically (P < 0.05). The SID lysine requirements for BWG and gain:feed were 1.06% and 1.08% for the one-slope broken-line, 1.17% and 1.22% for the quadratic broken-line, 1.11% and 1.16% for 95% of the upper asymptote of the quadratic model, and 1.12% and 1.17% for the first intercept between the plateau of the one-slope broken-line and quadratic models, respectively. In conclusion, the SID lysine requirements of Ross 308 broilers at the age of 10 to 21 days ranged from 1.06% to 1.17% for BWG and from 1.08% to 1.22% for gain:feed.